Magnitude of Toluene Exposure Risk in Digital Printing in Kendari City - Atmin, Asrif; Azizi Jayadipraja, Erwin; Harun, Aziz (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Initial survey of the number of Printing companies in Kendari City as many as 20 companies, the production produced includes printing billboards, banners, invitation printing industry, stickers, business cards, screen printing industry for cloth, clothes and other basic materials. Shows that workers in the printing company will be at great risk of exposure to chemicals in the production process while working in printing. So the author conducted a study entitled Analysis of Toluene Exposure Risk in Digital Printing Industry Workers in Kendari City. Method: The study used a quantitative approach with a descriptive survey method, the sample consisted of 100 employees, with detailed evaluations of 35 respondents in 7 locations. Air measurements were conducted on December 20, 2022 to determine the concentration of toluene, which ranged from 0.051 to 0.118 ppm. Result: The majority of respondents had a high school education (82.86%), were over 30 years old (57.14%), and were male (91.43%). Although the toluene concentration was far below the threshold of 50 ppm, the highest Intake (I) value was recorded at 0.481 mg/kg/day. Of the 35 HQ values analyzed, 15 exceeded 1, indicating a high health risk. In addition, 32 RQ values indicated a high carcinogenic risk. Conclusion: The need for good risk management even though toluene concentrations are within safe limits and the variation in health risks among workers indicates the importance of continuous monitoring and better risk management.